The Influence of Product Quality Comparative Testing Results on the Market - Ruževičius, Juozas (Ekonomika, 2005)
The main purpose of this article has been to prove the influence of product quality comparative testing results on the market, to demonstrate the importance of comparative testing of consumer products as a means of consumer information and consultation, to analyse its methodology and impact on market structures as well as on the behaviour of companies and consumers, and to determine possibilities for the practical application of comparative testing in Lithuania. The key objectives have been to analyse the framework of Lithuanian governmental institutions and public organisations responsible for the formulation and implementation of consumer policies, and their capabilities to perform product testing. In addition, peculiarities of the consumer market as well as the need for product information, which are both important factors for product testing, have been overviewed.Utilising comparative product testing methodology and research on how test results could be applied, it can be said that the formation of an independent, well-informed consumer base able to make calculated decisions requires planned and concentrated governmental efforts. Comparative product testing is one of the tools available for consumer education and information. Its significance and effectiveness in creating a consumer society such as this cannot be denied.When creating a comparative product testing system in Lithuania we need to take into account the experience of other Western countries in this field, as well as the potentiality of Lithuanian institutions to prepare and conduct testing of certain products. Research shows that at present in Lithuania it is food products which lend themselves most readily to product testing, while services fare worst. From the technological and economic viewpoints, co-operation among the Baltic States and any prior specialisation in this area would be useful when conducting product quality comparative testing.